(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the development of students’ functional literacy through cluster-based integrated learning in primary education. Functional literacy is understood not only as the ability to read and write but also as the capacity to apply knowledge, skills, and competencies to solve real-life problems in diverse contexts. The study highlights the significance of using cluster-based approaches, where subjects are interconnected and taught in an integrated manner, allowing students to acquire holistic knowledge while enhancing their problem-solving, communication, and critical thinking abilities. The article emphasizes that integrated cluster learning supports interdisciplinary understanding, promotes motivation, and prepares students for lifelong learning. The methodology includes a review of pedagogical practices and analysis of how cluster-based instruction fosters functional literacy through project work, group tasks, and practical activities. The results indicate that when primary school students engage in cluster-integrated learning, they demonstrate higher levels of comprehension, creativity, and self-expression, which contribute to the formation of functional literacy skills. The study concludes that cluster-based integrated learning offers an effective pedagogical strategy to prepare young learners for the challenges of the modern world and to strengthen their ability to adapt knowledge to practical situations.